Size effects in ultrafine iron. New structures: 2D - 3D (Nexo Revista Científica, 2021)
This article is devoted to the analysis of the size of iron nanoparticles impact on the structure, to comparison of the results obtained for the nanopowders in the various authors’ researches. The article considers factors that may impact on the form and parameters of the Mössbauer spectra of iron nanopowders obtained by the inert gas condensation technique (Gen-Miller’s method). Possible causes of the new state of the iron are proved with the effective magnetic field at the 57 Fe nucleus (H=365 kOe). But the results related to size effects differ from the researches of other authors. It was revealed that nanoparticles with a mean (X-ray data) particle size of 50 nm have also Angstrem patterns, which can meet the new structure. Presence of small amounts of superparamagnetic oxide could be a catalyst, impetus for the formation of the new structure, and also, at the exchange interactions, could modify the charge of the electron density at the Fe nuclei. Reviewed and other factors can result in appearing of such a high value of the effective magnetic field at the iron nuclei.